Infinispan data grid platform : making use of data grids for performance and scalability in Enterprise Java, using Infinispan from JBoss /: making use of data grids for performance and scalability in Enterprise Java, using Infinispan from JBoss. (2012) - Marchioni, Francesco; Surtani, Manik
No abstract available